Citative or Reportative Evidentiality in Reports Written in Spanish - Hernández Moya, Ingrid (2023)
This article addresses the study of evidentiality as the conceptual-functional category responsible for demonstrating the source of information. Therefore, we analyze evidenciality in the newspaper Juventud Rebelde. Its analysis serves to observe the functions that the chosen evidential units exercise in the construction of sense effects such as reliability, credibility, and/or (dis)compromise before what has been said. In addition, evidenciality is analyzed with a functionalist basis, such as that of the Functional Discourse, proposed by Grammar Hengeveld and Mackenzie (2008), and under the precepts of a qualitative methodology, supported by quantitative tools. This research is aimed to identify the different uses of these subcategories and analyzes their relationship with the pragmatic categories in the selected type of text. The work contributes to deepen this category from the functionalist perspective, little addressed in linguistic studies in Cuba.